Optimasi Konversi Energi Potensi Biodegradable Waste - Mochammad Junus; Indra Lukmana Putra; Asalil Mustaini; Nugraha Wijayanto; Nurefa Maulana (Ikatan Cendekiawan Muda Akuntansi, 2026)
Green sustainability accounting emphasizes the utilization of biodegradable waste by transforming costs into energy. TPST 3R Mulyoagung Bersatu in Dau District is one of the community-based waste management initiatives, yet it faces challenges such as limited human resources, outdated technology, and an aging workforce. The average organic waste generated reaches 5 tons per day, but only 3.5 tons are processed, while the remainder leads to additional treatment costs. This community service program was carried out in stages, including socialization, training, application of automatic waste sorting technology and biogas reactors, mentoring, and strengthening sustainability through the establishment of self-managed community groups. The results show improved waste management capacity, optimized sorting, a 80% increase in managerial skills, a 20% reduction in operational costs, and a 50% increase in compost and biogas production. The program contributes to the achievement of SDGs 8, 11, 12, and 13, generating dual benefits of a cleaner environment and new economic opportunities. In conclusion, integrating technology with community empowerment effectively reduces costs, addresses organic waste problems, and should be supported through policy expansion and replication of the model in other areas of Malang Regency.